668 IMPROVING ACCESS TO CALL BELLS: LESSONS FROM THE PANDEMIC. (8th March 2022) - Morrow, A; Knighton, A
Abstract: Introduction: Call bells are a simple safety measure linked to prevention of falls. The National Audit of Inpatient falls 2017 highlighted that access to call bells was highly variable across trusts and recommended regular auditing. The national average of access to call bells was 81%. The winter covid pandemic posed a significant burden on staffing levels due to absence and redeployment. Experienced nursing staff are essential to maintaining good quality care to elderly patients. Method: We conducted an audit of access to call bells on a geriatric ward in December 2020 (mid-pandemic) compared to April 2021 (post-pandemic). Patients receiving 1:1 or cohort nursing care were not included. Result A total of 40 patients were audited. Mean age mid-pandemic was 88.7 compared to 86.4 post-pandemic. The average frailty score was 5.4 and 5.5 respectively. 47.4% of patients mid-pandemic had a documented dementia or delirium, versus 28.6% post-pandemic. The percentage of patients with access to a call bell mid-pandemic was 42.1% compared to 85.7% post-pandemic, a statistically significant difference (χ2 = 8.3, P = 0.004). Relative risk of call bell unavailability was 4.1 times greater in the December cohort than in April (RR 4.1, 95% CI 1.3–12.4). Staffing was reported to be below expected levels in December 2020 with not all nurses/HCAs having experience in geriatric care compared to expected staffing levels of experienced ward staff in April 2021. Conclusion: Access of call bells to elderly patients remains a simple intervention in preventing inpatient falls. In light of the threat of new covid variants and future winter pressures we remain hopeful that the importance of adequate levels of experienced nursing staff for our elderly population is not underestimated. We are currently implementing a '5 moments for call bell access' quality improvement project and recommend further auditing across departments within the Trust.